Burden and trends of antimicrobial non-susceptibility in skin and soft tissue infections: nine-year microbiological surveillance from a tertiary hospital in Riyadh, Saudi Arabia - Shabi, Yahya; Alshehri, Abdullah A.; Binkhamis, Khalifa; Alqahtani, Mohammed; Alsaeed, Thamir Saad; Aljaberi, Ali Abdullah; Alkhamis, Saleh Abdullah; Alshomrani, Mohammad K.; Almutairi, Abdullah Z.; Alqahtani, Abdulah J.; Bosaily, Ahmad Jebril M.; Alshahrani, Fatimah (Frontiers in Microbiology, 2026)
BackgroundSkin and soft tissue infections (SSTIs) impose a substantial global and regional burden, and their management is increasingly complicated by antimicrobial non-susceptibility. In Saudi Arabia, data remain fragmented, with few studies providing species-level analyses stratified by specimen type and infection depth.MethodsWe retrospectively analyzed 6,760 wound and tissue specimens (2016–2024) from a tertiary hospital in Riyadh, Saudi Arabia. Organisms were identified using standard microbiological methods and VITEK 2. Antimicrobial susceptibility testing was interpreted according to CLSI M100, defining non-susceptibility as resistant or intermediate categories. Binary logistic regression was used to assess temporal trends in antimicrobial non-susceptibility, with year of isolation entered as a continuous predictor.ResultsGram-negative organisms predominated (63.2%), followed by Gram-positives (35.6%) and yeast (1.2%). Staphylococcus aureus was the leading pathogen (28.8%), with methicillin resistance detected in 39.0% of isolates. Escherichia coli (14.7%) and Pseudomonas aeruginosa (12.1%) were also common. Among Enterobacterales, 26.9% were extended-spectrum β-lactamase (ESBL) producers and 16.1% were carbapenem-resistant Enterobacterales (CRE). P. aeruginosa showed high carbapenem non-susceptibility. Tissue-derived isolates demonstrated significantly higher meropenem non-susceptibility than swab Isolates (20.3% vs. 16.4%, p = 0.027), although Enterobacterales subsets occasionally showed the reverse pattern. Temporal analysis revealed rising non-susceptibility to amikacin, ceftriaxone, imipenem, and meropenem (p < 0.05), while oxacillin resistance in S. aureus and clindamycin non-susceptibility in Gram-positives declined over time.ConclusionGram-negative organisms predominated in SSTIs, showing rising non-susceptibility to amikacin and carbapenems. Separately, among Gram-positive pathogens, S. aureus exhibited a clear decline in oxacillin resistance. These shifts underscore the need for ongoing resistance surveillance.